GAMBAR PENGETAHUAN IBU HAMIL TENTANG PENTINGNYA PERSALINAN DI FASILITAS KESEHATAN DI DESA CIPACING KECAMATAN JATINANGOR - Fardila Elba; Okta Arba'ah Afifah (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2021)
During pregnancy time it is necessary to there are a lot of changes that accured to mother. The necessery of that knowledge can be used to make decision when something change or happen during pregnancy and maternity. This research aims to find out pregnant mother knowledge based on there characteristic, such us age, education, occupation, and parity on how do they choose the maternity and also place of maternity. The main method that is used on this research is cross sectional descriptive method. The data source comes from 58 people that are matched with specific criteria. This uses questionnaire it is obtained from Cipacing Village. The results of this research is to give the education of pregnant mother in the Cipacing Village to have some good knowledge about the selection of health facilities and the birth attendant with the percentage amount of 62.1% pregnant women in the Cipacing Village and obtained on the research results about the mother's knowledge based on resources that have the knowledge either through the midwife / relatives / family was 61.1%. The conclusion of this research needs to be more developed the information about pregnancy and maternity still needs to be given in classes, such us the efforts to acknowledge the dangerous signs, maternity preparation, and how to us how assurance. It is the obligations of our people to educate them, so that in the future, pregnancy mother’s have better knowledge about pregnancy and maternity. Keywords: health facility, knowledge, maternity